Dbx1-Derived Pyramidal Neurons Are Generated Locally in the Developing Murine Neocortex - Rueda-Alaña, Eneritz; Martínez-Garay, Isabel; Encinas, Juan Manuel; Molnár, Zoltán; García-Moreno, Fernando (Frontiers in Neuroscience, 2018)
The neocortex generates at the dorsal region of the pallium in the forebrain. Several adjacent structures also contribute with neurons to neocortex. Ventral pallium is considered to generate several populations of neurons that arrive through tangential migration to the neocortex. Amongst them are the Cajal-Retzius cells and some transient pyramidal neurons. However, the specific site and timing of generation, trajectory of migration and actual contribution to the pyramidal population remains elusive. Here we investigate the spatio-temporal origin of neuronal populations from ventral pallium in an in vivo model, using a transposase mediated in utero electroporation method in embryonic mouse in vivo. From E11 to E14 cells born at the lateral corner of the neocortical neuroepithelium including the ventral pallium migrated ventro-laterally to settle all areas of the ventral telencephalon. Specifically, neurons migrated into amygdala, olfactory cortices and claustrum. However, we found no evidence for any neurons migrating tangentially towards the neocortex, regardless the antero-posterior level and developmental time of the electroporation. Our results challenge the described ventral-pallial origin of the transient pyramidal neuron population. In order to find the exact origin of cortical neurons that were previously Dbx1-fate mapped we used the promoter region of the murine Dbx1 locus to selectively target Dbx1-expressing progenitors and label their lineage. We found these progenitors in low numbers in all pallial areas, and not only in the ventral pallial ventricular zone. Our findings on the local cortical origin of the Dbx1-expressing pyramidal neurons reconcile the observation of Dbx1 expressing neurons in the cortex without evidence of dorsal tangential migration from ventral pallium and provide a new framework for the origin of the transient Dbx1-derived pyramidal neuron population. We conclude that these neurons are born locally within the dorsal pallial neuroepithelium.